From a town to an attraction: the transformation of Ohrid, North Macedonia - Biljana Petrevska; Noga Collins-Kreiner (Boletín de la Asociación de Geógrafos Españoles)
This article assesses the different forces involved in shaping the city of Ohrid (North Macedonia) and demonstrates the manner in which the city has been transformed by tourism development. As a post-socialist city, the development of Ohrid has unique characters in terms of landscape, economic dynamics, and functional dimensions. The study's aim is also achieved by analyzing the validity and applicability of the Tourism Area Life Cycle (TALC) model with regard to the evolution of tourism development in Ohrid, specifically, and in other cities in general. The article emphasizes the connection between the city’s urban context and tourism development. The findings also indicate that Ohrid is currently in its Development stage and that its life cycle curve exhibits a double cycle sequence, meaning that Ohrid is attracting many visitors and has reached a state of tourism maturity. The article emphasizes the connection between the city’s urban context and tourism development. From a practical perspective, the study reveals a lack of urban planning and uncontrolled tourism development.